Multisequencing of problem of synthesis of optimal structure of complexing calculator in flying vehicles course system - Жуков, И. А.; Аль-Раббат, С. (Proceedings of National Aviation University (archive), 2000)
Considered is multi sequencing of solution of the problem of synthesis of optimal complexing calculator structure in course system which accelerates construction of amplitude-phase characteristics of each part of complexing calculator and allows to visually trace, with the help of the introduced characteristics, the change of parameters of information transportation algorithms in flying conditions